Trends in criminal policy: (dis) organising the chaos. Execute cannot have mercy (where is the comma). Crime vs state, state vs crime. Decriminalisation - Туляков, В. О.; Tuliakov, Viacheslav O.; Туляков, Вячеслав Алексеевич (Ciudad Real, 2023)
• Principles of effective penalization • United against… Towards new system of security • Sanctions vs cash flows • Compensate and restitute not prosecute • And sun always rises (how to prosecute criminals effectively

• International approach • European approach • Local developments • Violence • Economy • Drug abuse

• Principles of decriminalization • Diversification vs flexibility • Concept of Public law code • Victim-oriented CC
Tuliakov V. О. Trends in criminal policy: (dis) organising the chaos. Execute cannot have mercy (where is the comma). Crime vs state, state vs crime. Decriminalisation [Electronic resource] : lecture 6\8 : [presentation PowerPoint] / V. О. Tuliakov. – Electronic data (17 slides). – Ciudad Real, 2023. – Режим доступу : https://hdl.handle.net/11300/25989
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; effective penalization; system of security; Sanctions